Formal Concept Analysis : 13th International Conference, ICFCA 2015, Nerja, Spain, June 23-26, 2015, Proceedings - Baixeries, Jaume; Sacarea, Christian; Ojeda-Aciego, Manuel; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 13th International Conference on Formal Concept Analysis, ICFCA 2015, held in Neja, Spain, in June 2015. The 16 revised full papers presented were carefully reviewed and selected from 38 submissions. The topics in this volume cover theoretical aspects of FCA; methods and applications of FCA to different fields and enhanced FCA that show new trends in FCA, for instance, pattern structures of fuzzy FCA.
Theoretical aspects of FCA -- Methods and applications of FCA to different fields -- Enhanced FCA that show new trends in FCA -- Pattern structures of fuzzy FCA.
Keywords: Artificial intelligence; Software engineering; Data mining; Computer science; Computational complexity; Algebra; Artificial Intelligence; Software Engineering; Data Mining and Knowledge Discovery; Mathematical Logic and Formal Languages; Discrete Mathematics in Computer Science; Order, Lattices, Ordered Algebraic Structures